Optogenetic fMRI in the mouse hippocampus: hemodynamic response to brief glutamatergic stimuli - Lebhardt, Philipp; Sartorius, Alexander (Journal of cerebral blood flow & metabolism, 2016)
The combination of optogenetics with functional magnetic resonance imaging is a promising tool to study the causal relationship between specific neuronal populations and global brain activity. We employed this technique to study the brain response to recruitment of glutamatergic neurons in the mouse hippocampus. The light-sensitive protein channelrhodopsin-2 was expressed in α-CamKII-positive glutamatergic neurons in the left hippocampus (N = 10). Functional magnetic resonance imaging was performed during local laser stimulation, with stimulus duration of 1 second. The hemodynamic response to these stimuli was analyzed on a whole-brain level. In a secondary analysis, we examined the impact of the stimulation locus on the dorso-ventral axis within the hippocampal formation. The hemodynamic response in the mouse hippocampus had an earlier peak and a shorter duration compared to those observed in humans. Photostimulation was associated with significantly increased blood oxygen level-dependent signal in group statistics: bilaterally in the hippocampus, frontal lobe and septum, ipsilaterally in the nucleus accumbens and contralaterally in the striatum. More dorsal position of the laser fiber was associated with a stronger activation in projection regions (insular cortex and striatum). The characterization of brain-region-specific hemodynamic response functions may enable more precise interpretation of future functional magnetic resonance imaging experiments.